KEBIJAKAN MONETER DAN IMPLIKASINYA TERHADAP STABILITAS EKONOMI MAKRO DI INDONESIA: STUDY SYSTEMATIC LITERATURE REVIEW (SLR) - Syifa Athaya; Syafriandi Aziz; Siti Fahira Sihotang; Hj. Yenni Samri Juliati Nasution (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study aims to systematically review the literature on monetary policy and its impact on macroeconomic stability in Indonesia. Using the Systematic Literature Review method, this study evaluates 10 high-quality journals published between 2020 and 2025. The review shows that monetary policy, particularly through the instruments of benchmark interest rates, open market operations, minimum reserve requirements, and foreign exchange market interventions, plays a significant role in controlling inflation, maintaining exchange rate stability, and promoting economic growth. The findings also show that the response of the Indonesian economy to changes in interest rates and money supply is consistent, but policy effectiveness still faces challenges such as imperfections in policy transmission, global influences, and developments in financial technology. Therefore, an adaptive, credible, and coordinated monetary policy with fiscal policy is needed to achieve sustainable macroeconomic stability.